Using narratives to understand progress in youth alcohol and other drug treatment - Wilson, Mandy; Saggers, Sherry; Wildy, H. (Emerald Group Publishing, 2013)
Purpose – This paper aims to illustrate how narrative research techniques can be employed to promote greater understanding of young people’s experiences of progress in residential alcohol and other drug treatment. Design/methodology/approach – Narrative inquiry is used to explore client understandings of what characterises progress in treatment for young people attending a residential detoxification and a residential rehabilitation service in Perth, Western Australia. This article focuses on stories of progress collected through in-depth qualitative interviews, observation and participation with clients of the two services, over a five-month period. Findings – Analysis of data revealed that young people were able to vividly describe their progress through treatment, and their drug taking trajectories can be conceptualised along five stages. The authors prepared narrative accounts to illustrate the features characteristic of each stage as identified by the young people. These composite narratives, written from the perspectives of young people, are presented in this article. Practical implications – Clients’ own perceptions of their journeys through drug treatment might enable staff of such services to collaborate with the young person, in shaping and positively reinforcing alternative life-stories; from those of exclusion and disconnection, to narratives of opportunity, inclusion and possibility. Originality/value – Harmful adolescent drug and alcohol use is on the rise in Australia and elsewhere. However, our knowledge of how young people experience progress through residential treatment for substance use is limited. This paper highlights how creating narratives from young people’s own stories of progress can broaden our knowledge of “what works” in residential youth alcohol and other drug treatment services.